1986
DOI: 10.1039/p29860000629
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of phospholes with acids; [1,5] proton shifts in 1H-λ5-phospholes

Abstract: Addition to phospholes of gaseous HCI at -90 "C or of an excess of trifluoromethanesulphonic acid at -70 "C, results in P-protonation. The triflate solutions are stable up to room temperature, but the 1 Hphospholium chlorides form P V adducts at -70 "C, which rapidly rearrange by a [1,5]sigmatropic Hshift. The observed product is a 1 -chloro-2,5-dihydrophospholium chloride. Addition of a chloride ion source to the triflates produces the same result. Unprotonated 3,4-dimethyl-1 -phenyl phosphole was found to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…1W-Phospholes 1. Nucleophilic Properties of Phosphorus The reaction of phospholes with acids was understood only very recently. 124 It leads to phospholene derivatives that formally result from the protonation of the phosphole ring at carbon. Two such reactions have been described.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…1W-Phospholes 1. Nucleophilic Properties of Phosphorus The reaction of phospholes with acids was understood only very recently. 124 It leads to phospholene derivatives that formally result from the protonation of the phosphole ring at carbon. Two such reactions have been described.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…C 2015 Wiley Periodicals, Inc. justified by semiempirical calculations [6]. The results of Quin, Mathey, and other authors revealed the importance of the 7-phosphanorbornene derivatives in fragmentation-related phosphorylation reactions [7][8][9], complexations [10][11][12], and in re-functionalizations [13][14][15][16] including deoxygenations [17][18][19]. The Bayer-Villiger oxidation of 7-phosphanorbornenes leads to valuable oxaphosphabicyclo [2.2.2]octene derivatives that may be useful in fragmentation-related phosphorylations [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The second method relies on the dehydrohalogenation of diene-dihalophosphine cycloadducts [24]. The postulated mechanism is depicted in Scheme 23.2 [25].…”
Section: Spectral Structural and Theoretical Studiesmentioning
confidence: 99%
“…The P-H þ salts are only stable when the counterion (e.g., TaCl 6 À ) does not display any coordinating ability [39]. Otherwise they evolve to give phospholene oxides via a pentacoordinate intermediate and a [1,5]-shift of H [25]. The oxides tend to dimerize via a [4 þ 2] Diels-Alder reaction and display a limited life time at room temperature [40] except when heavily substituted on the ring.…”
Section: Reactions At Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation